Optimalisasi Rantai Pasok Pangan Lokal dalam Program Makan Bergizi Gratis (MBG): Studi Kasus Integrasi UMKM dan Satuan Pelayanan Pemenuhan Gizi (SPPG) di Kab. Kendal - Dina Ulayya Aziizah; Luthfi Arie Widzayanto; Muarifudin Muarifudin; Ripan Ripan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study analyzes strategies to optimize the local food supply chain for the Free Nutritious Meal Program (MBG) in Kendal Regency by integrating MSMEs with Nutrition Fulfillment Service Units (SPPG). Using a qualitative case study approach, the research identifies structural barriers such as seasonal production fluctuations, limited cold chain infrastructure, and inconsistent quality standards. To address these, the study proposes a supply chain model focused on strengthening MSME institutions through long-term partnerships and data-driven logistics systems. Key recommendations include local government incentives and accelerated development of post-harvest facilities. The results suggest that solid MSME-SPPG integration will not only improve community nutrition but also drive the local economy and enhance regional food self-sufficiency. By aligning local production with SPPG needs, Kendal Regency can transform a national program into a sustainable catalyst for economic growth.